KARAKTERISASI SIFAT FISIS DAN KEKERASAN PISTON SEPEDA MOTOR SUZUKI DAN PISTON SEPEDA MOTOR DENSHIN - RONALD NAIBAHO (LP2MTBM MAKARIOZ, 2020)
The purpose of this study was to determine the Chemical Composition, Micro Structure and hardness of the new piston types of SUZUKI and DENSHIN motorcycles. The research method begins with the preparation of the piston material, making the specimen, conducting the test and discussing it. Chemical composition test results show that the two pistons are Al-Si Hypoeutectic alloys with a percentage of Si that does not exceed the Eutectic limit of 12.6% (Si). Ingredients, SUZUKI 0.1045% (Cu) 0.0009% (Ni), DENSHIN 0.1351% (Cu) 0.0021% (Ni). The results of the photo observation of the Micro Structure Test of SUZUKI and DENSHIN piston specimens showed that the Si phase forms were almost as smooth and evenly distributed. The Hardness Test results show that the SUZUKI and DENSHIN pistons have almost the same hardness value.